J2EE 1.4 the big picture - Haugland, Solveig (Prentice Hall, 2004)
In short, J2EE is a powerful, but complex technology. J2EE is many things, but essentially it is a standard for application servers. In this innovative new book, the authors provide a concise and entertaining introduction to the J2EE platform for professionals who need to understand the big picture, and may or may not be technically savvy. The book provides an overview of the four key tiers in J2EE and how they work, at a level anyone can understand. This book is tightly focused on J2EE and will not address competing technologies or extended implementation or specific development or deployment details.